2011
DOI: 10.1111/j.1755-0238.2011.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Grape root cell features related to phylloxera resistance and changes of anatomy and endogenous hormones during nodosity and tuberosity formation

Abstract: Background and Aims:  Cell wall anatomical and chemical components of different phylloxera resistant grapevine roots were examined. Changes in anatomy and endogenous hormone levels were tested during phylloxera‐induced nodosity and tuberosity formation. Methods and Results:  Tertiary roots of 3–5 mm diameter from 4‐year‐old grapevines with different phylloxera resistance ratings were collected in September to examine cellular anatomy and endogenous hormones in nodosities and tuberosities. Grapevine roots with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…A previous study showed that the lignin, cellulose and pectin content varied between strains; the order was rootstocks > V. amurensis × V. vinifera > V. vinifera × V. labrusca , V. vinifera . The phylloxera‐resistance of these cultivars was consistent with the lignin, cellulose and pectin content (Wang et al , Du et al ), the anatomical structure was influenced by the chemical composition, and the greater the lignin, cellulose and pectin content the more compact the cells. Anatomical structure and chemical composition affect the rate of phylloxera stylet penetration (Du et al ), suggesting firmness of the roots may be determined by the structure and chemical composition.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…A previous study showed that the lignin, cellulose and pectin content varied between strains; the order was rootstocks > V. amurensis × V. vinifera > V. vinifera × V. labrusca , V. vinifera . The phylloxera‐resistance of these cultivars was consistent with the lignin, cellulose and pectin content (Wang et al , Du et al ), the anatomical structure was influenced by the chemical composition, and the greater the lignin, cellulose and pectin content the more compact the cells. Anatomical structure and chemical composition affect the rate of phylloxera stylet penetration (Du et al ), suggesting firmness of the roots may be determined by the structure and chemical composition.…”
Section: Discussionsupporting
confidence: 60%
“…The phylloxera‐resistance of these cultivars was consistent with the lignin, cellulose and pectin content (Wang et al , Du et al ), the anatomical structure was influenced by the chemical composition, and the greater the lignin, cellulose and pectin content the more compact the cells. Anatomical structure and chemical composition affect the rate of phylloxera stylet penetration (Du et al ), suggesting firmness of the roots may be determined by the structure and chemical composition. The anatomical structure and chemical composition of roots was significantly correlated with cold hardiness (Gao et al ), and grape cultivars with thick root exodermis layers, thin phloem and a high proportion of xylem had better cold hardiness than the other cultivars.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Even so, earlier studies have provided some evidence of physiological changes in nodosities upon attack by this insect (e.g. Forneck et al 2001b ; Kellow et al 2004 ; Du et al 2011 ) arguing that not only genes involved in cell wall modification are affected. Thus, further enzymatic changes expressed in increased activity of peroxidase, acidic phosphatase and leucine aminopeptidase have also been shown upon phylloxera attack (Forneck et al 2002 ).…”
Section: Discussionmentioning
confidence: 97%